p53 dephosphorylation and p21(Cip1/Waf1) translocation correlate with caspase-3 activation in TGF-beta 1-induced apoptosis of HuH-7 cells - Fan, G (2015)
The p53 tumor suppressor gene product plays an important role in the regulation of apoptosis. Transforming growth factor beta1 (TGF-beta1)-induced apoptosis in hepatic cells is associated with reduced expression of the retinoblastoma protein (pRb) and sub